Autonomous management in contemporary art territory (Argentina 2001-2015). A methodological proposal from the possibilities of the ARS - Benito, Patricia Virginia (AWARI, 2020)
The present work addresses the autonomous management in Argentine art between 2001 and 2015. The proposed analysis approach focuses on the concept of territory from a transdisciplinary perspective and in particular, in relation to the field of contemporary visual arts. In this sense, the question that shapes our work is whether these projects, which perceive themselves as autonomous, achieve real sovereignty based on their practices, or are they subject to geopolitical decisions that always end up conditioning them?. In this way, we work in the first instance with the data collected by the C.A.R.A., and later a methodological design is carried out that allows us to configure two cartographic proposals based on the ARS working synchronously with the networks and matrices obtained. From which it is sought to graph, through the UCINET software, the autonomous management in the territory and, in turn, to create a relational chromatic matrix based on behavioral registers that allow us to form a mapping of the symbolic territory towards the interior of the procedures. The results obtained give an account of a historical perspective of the autonomous management projects in the country, how the distribution of this type of proposals has been in relation to 6 regions that are governed by administration policies of the national cultural heritage, and finally, of the configuration of its own territory in which it is observed how the ways of operating the set of procedures surveyed have been in relation to the agenda of activities, the sources of financing and the communication channels used.